Design of goods lift - Chen, Rongkai. (2008)
This dissertation describes the application of the generic product design process in the design and development of a goods lift mean for a local building.The enhancement of goods lift in terms of performance features including improvement in hauling capacity, and reduced travelling time, improved quality and reliability, and a significant reduction of manufacturing cost have been achieved by adopting proper control of the product design process. Comprehensive information of design of the goods lift is also presented.